2017
DOI: 10.3892/or.2017.5675
|View full text |Cite
|
Sign up to set email alerts
|

The blueberry component pterostilbene has potent anti-myeloma activity in bortezomib-resistant cells

Abstract: Abstract. Multiple myeloma (MM) is an incurable hematologic malignancy because of its drug resistance. Pterostilbene (Pter) is found mainly in blueberries and grapes. The effects of Pter and its exact pharmacologic mechanisms on chemoresistant myeloma are not known. Herein, we investigated the anti-myeloma activity of Pter in bortezomib-resistant cell line H929R and explored the related mechanism of action for the first time. We found that Pter inhibited proliferation of H929R cells and promoted apoptosis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Multiple studies have reported that natural products derived from plants are important sources of drugs that may offer significant treatment for the majority of cancer types, including colorectal and oral cancer ( 41 , 42 ). Consistent with previous studies, in which it was observed that PTE inhibited MM cell viability and induced cell cycle arrest through regulating the mitogen-activated protein kinase pathway ( 43 , 44 ), the present study demonstrated that the administration of PTE could induce MM apoptosis in vitro , and decrease tumor burden in vivo . Additionally, to the best of our knowledge, the present study was the first to report that PTE-induced MM apoptosis was metabolically dependent, via the activation of AMPK, in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 92%
“…Multiple studies have reported that natural products derived from plants are important sources of drugs that may offer significant treatment for the majority of cancer types, including colorectal and oral cancer ( 41 , 42 ). Consistent with previous studies, in which it was observed that PTE inhibited MM cell viability and induced cell cycle arrest through regulating the mitogen-activated protein kinase pathway ( 43 , 44 ), the present study demonstrated that the administration of PTE could induce MM apoptosis in vitro , and decrease tumor burden in vivo . Additionally, to the best of our knowledge, the present study was the first to report that PTE-induced MM apoptosis was metabolically dependent, via the activation of AMPK, in vitro and in vivo .…”
Section: Discussionsupporting
confidence: 92%
“…Mitochondria benefits from the protective effects of blueberry anthocyanin extract against acrylamide toxicity [ 28 ]. Pterostilbene in blueberries can control worsened/obdurate myeloma therapy and major therapeutic myeloma of bortezomib chemotherapy [ 29 ]. Lowbush blueberry proanthocyanidins can enhance apoptosis induction in human colorectal cancer cell lines, which represents important nutritional chemoprevention of colorectal cancer [ 30 ].…”
Section: Preventive Chronic Disease Of Blueberrymentioning
confidence: 99%
“…Pterostilbene (or 3′,5′-dimethoxyresveratrol) is a compound found in blueberries and grapes [ 85 ]. Pterostilbene was investigated on H929 and bortezomib-resistant H929R cell lines, showing IC 50 values of 22.83 and 34.80 µM, respectively, after 48 h of incubation.…”
Section: Resultsmentioning
confidence: 99%